The DEK Oncogene Is a Target of Steroid Hormone Receptor Signaling in Breast Cancer - Privette Vinnedge, Lisa M. (Public Library of Science, 2012)
Expression of estrogen and progesterone hormone receptors indicates a favorable prognosis due to the successful use of hormonal therapies such as tamoxifen and aromatase inhibitors. Unfortunately, 15–20% of patients will experience breast cancer recurrence despite continued use of tamoxifen. Drug resistance to hormonal therapies is of great clinical concern so it is imperative to identify novel molecular factors that contribute to tumorigenesis in hormone receptor positive cancers and/or mediate drug sensitivity. The hope is that targeted therapies, in combination with hormonal therapies, will improve survival and prevent recurrence. We have previously shown that the DEK oncogene, which is a chromatin remodeling protein, supports breast cancer cell proliferation, invasion and the maintenance of the breast cancer stem cell population. In this report, we demonstrate that DEK expression is associated with positive hormone receptor status in primary breast cancers and is up-regulated in vitro following exposure to the hormones estrogen, progesterone, and androgen. Chromatin immunoprecipitation experiments identify DEK as a novel estrogen receptor α (ERα) target gene whose expression promotes estrogen-induced proliferation. Finally, we report for the first time that DEK depletion enhances tamoxifen-induced cell death in ER+ breast cancer cell lines. Together, our data suggest that DEK promotes the pathogenesis of ER+ breast cancer and that the targeted inhibition of DEK may enhance the efficacy of conventional hormone therapies.